The role of solvent type, size and chemical composition of bioactive glass particles in modulating material properties of poly(ε-caprolactone) based composites. (November 2016) - Dziadek, Michal; Zagrajczuk, Barbara; Ziabka, Magdalena; Dziadek, Kinga; Cholewa-Kowalska, Katarzyna
Abstract: The role of solvent type (dichloromethane, 1, 4-dioxane, tetrahydrofuran), size (<45, <3 μm) and chemical composition (silica-rich, calcium-rich) of bioactive glass (BG) particles in modulating surface properties, crystallinity, mechanical properties and in vitro bioactivity of poly(ε-caprolactone) based composite films was investigated. Films were prepared by solvent casting method. Bioactive glasses from the SiO2 –CaO–P2 O5 system were obtained by sol-gel method. The particle size and solvent type played an important role in nucleation and crystallisation kinetics of PCL, affecting morphology, topography and wettability of films. In contrast to BG particles of <45 μm size, the smaller ones (<3 μm) were exposed on the surfaces of films and consequently have improved hydrophilicity and have provided crystallisation of carbonated hydroxyapatite after incubation in SBF. Type of the solvent, by affecting surface properties, influenced hydroxyapatite crystallisation process. The addition of BG particles of both sizes resulted in enhanced modulus and drastic decrease in elongation at break.